2015
DOI: 10.1016/j.msec.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel simple one-step air jet spinning approach for deposition of poly(vinyl acetate)/hydroxyapatite composite nanofibers on Ti implants

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…This technology has been reported as a one‐step low‐cost process with high production rate over short time based on the use of pressurized gas, which is dispensed at an extreme speed in order to stretch the polymer solution into thin fibers at the nozzle outlet. At the same instant, the solvent starts to evaporate and continues to do so after the fibers are deposited onto a substrate . Our results by SEM characterization demonstrated that we were able to collect and fabricate, by the AJT, PLA membrane scaffolds with nanometric, random fiber structure, where the concentration of PLA exerts a direct effect on the mean diameter size of the fibers.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This technology has been reported as a one‐step low‐cost process with high production rate over short time based on the use of pressurized gas, which is dispensed at an extreme speed in order to stretch the polymer solution into thin fibers at the nozzle outlet. At the same instant, the solvent starts to evaporate and continues to do so after the fibers are deposited onto a substrate . Our results by SEM characterization demonstrated that we were able to collect and fabricate, by the AJT, PLA membrane scaffolds with nanometric, random fiber structure, where the concentration of PLA exerts a direct effect on the mean diameter size of the fibers.…”
Section: Discussionmentioning
confidence: 72%
“…At the same instant, the solvent starts to evaporate and continues to do so after the fibers are deposited onto a substrate. 38,39 Our results by SEM characterization demonstrated that we were able to collect and fabricate, by the AJT, PLA membrane scaffolds with nanometric, random fiber structure, where the concentration of PLA exerts a direct effect on the mean diameter size of the fibers. This nanometric fiber structure could achieve the desirable functionality, mimicking the intricate interaction between cells and their microenvironment with respect to the ECM and our results are in accordance with recent studies using the AJT technology, that report similar fiber diameter structure and validate good biocompatibility properties of these spun mats.…”
Section: Discussionmentioning
confidence: 77%
“…This inert polymer has the advantage that it does not induce a deleterious reaction in living tissue (Sadato et al, 1994). Because of all these characteristics PVAc has been used in many medical fields, including drug and cell carries and in tissue engineering (Abdal-hay et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many studies to explore the compatibility of airbrush spraying with a number of polymers for production of nanofibers or thin films, there have been only a few studies on the compatibility of airbrush spraying with hydrogels. The possibility of in situ deposition of thermoresponsive hydrogels holds promise for a host of applications ranging from the treatment of burn wounds and ulcers to the regeneration of bone and cartilage tissue defects.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, researchers have explored the compatibility of spraying with a number of cell types, including epithelial and smooth muscle cells for coating tissueengineered constructs like trachea or bronchi, 16 keratinocytes and bovine dermal fibroblasts for chronic or burn wound healing, 17,18 and chondrocytes for cartilage repair. 14 Although there have been many studies to explore the compatibility of airbrush spraying with a number of polymers for production of nanofibers 13,[19][20][21][22][23][24][25][26][27] or thin films, [28][29][30] there have been only a few studies 31,32 on the compatibility of airbrush spraying with hydrogels. The possibility of in situ deposition of thermoresponsive hydrogels holds promise for a host of applications ranging from the treatment of burn wounds and ulcers to the regeneration of bone and cartilage tissue defects.…”
Section: Introductionmentioning
confidence: 99%